Identification of Polysaccharides From Dipsacus asperoides and Their Effects on Osteoblast Proliferation and Differentiation in a High-Glucose Environment - Xu, Duoduo; Liu, Jia; Zheng, Wei; Gao, Qipin; Gao, Yang; Leng, Xiangyang (Frontiers in Pharmacology, 2022)
Polysaccharides (DAI-1and DAI-2) from Dipsacus asperoides were obtained using mixed ion-exchange resin and Sephadex G-50 column chromatography then their properties, structures and activities were studied. The results demonstrated that DAI-1 and DAI-2 were homogeneous polysaccharides with molecular weights of 17kDa and 4kDa, respectively, that contained only glucose (Glc) residues. Results of methylation-based structural studies showed that backbones of DAI-1 and DAI-2 were composed of (1→6)-linked Glc residues. DAI-1 possessed a small number of side chains and a branch point of (1→3,6)- Glc, while DAI-2 lacked branching. Activity tests indicated that exposure of osteoblasts in a high-glucose environment to concentrations of DAI-1 of 25, 50 or 100 mg/ml induced cell proliferation and led to increased mRNA- and protein-level expression of bone morphogenetic protein 2 (BMP-2) and significantly promoted runt-related transcription factor 2 (Runx 2) expression. Moreover, DAI-1 treatment significantly increased alkaline phosphatase (ALP) and osteocalcin (OCN) activities in osteoblasts, suggesting that DAI-1 may exert activities that promote osteoblast proliferation and differentiation in a high-glucose environment.